(untitled) (Research, Society and Development, 2020)
This study aimed to analyze the antecedent factors associated with the coach athlete relatioship (CART) from the perspective of Brazilian coaches. 182 Brazilian coaches of both sexes, with an average age of 40.47 ± 9.7 years, participating in the 2015 Youth School Games were subjected. As instruments were used: identification form, Coach-Athlete Relationship Questionnaire (CART-Q coach version) and the Basic Needs in Sports Satisfaction Scale (BNSSS). Data were analyzed using descriptive and inferential statistics using Binary Logistic Regression (p <0.05). The results showed that the time of relationship had a significant association (p <0.20) with 3,410 times more likely to have high quality in the affective aspect of CART compared to a shorter time of relationship. The length of the relationship explained 2.927 more chances of occurring the presence of high quality cognitive aspects in periods of relationship over 4 years. It was observed that the time of experience explains in 2,655 more chances the satisfactory relationships, while the autonomy of the trainer explains in 2,589 more chances the presence of the cognitive aspect of the CART. Age and satisfaction of basic psychological needs (autonomy, competence and relationship) were associated with the quality of the commitment in the coach-athlete relationship (p <0.20). It is concluded that factors related to the relationship time, experience time, satisfaction of the basic psychological needs of autonomy and relationships in the sports context are favorable for quality relationships, in the perception of Brazilian coaches.